Contribuições do ensino de Ciências com enfoque CTS para o desenvolvimento do letramento científico dos estudantes - Victor Augusto Bianchetti Rodrigues (2017)
In the last decades, the specialized community has been dedicated to discussing changes in scholar education, aiming at the promotion of practices more coherent with the characteristics and the necessities of the contemporary society. Therefore, new teaching strategies are required. In science education, one of the innovative trends, which has gained prominence, is the thematic approach focused on the relationship between science, technology and society (STS). Many researches have credited the STS perspective as a way to leverage students' engagement in studying science. However, empirical results do not seem consensual with regard to the learning of scientific concepts. While some studiespresent results that endorse the STS perspective as a positive approach to support students learning of scientific concepts, other studies do not recognize the same potential. We consider the learning of scientific concepts as an important element for students to develop scientific literacy (SL). We have adopted a critical conception of SL, in whichscientific concepts have to be articulated as a tool for understanding the context in which students are inserted. Therefore, our study intended to advance the understanding about the contribution of STS approach to science education, more specifically, to the learning of scientific concepts and their application in contexts of social relevance. We developed aSTS didactic sequence on the theme "water" in the context of Adult Education. All the classes in which the didactic sequence was applied were audio and video recording. In addition, the students answered a multiple-choice questionnaire comprised by four questions that require the articulation of the scientific concepts addressed in the STS didactic sequence. The analysis of the results showed that the success rate in the multiplechoice questions was higher than usual. Our analyses indicate that some aspects supported the students learning of scientific concepts in STS approach: the use of problematic situations, the use of evidence and the use of a theme of social and scientific relevance. Inaddition, the students wrote two texts about the theme "water": one at the beginning and another at the end of the didactic sequence. The analysis of these texts showed that, after the STS didactic sequence, the students started to use the scientific dimension to position themselves in relation to the theme "water". We concluded that the STS didactic sequence made it possible for many students to use the knowledge produced in the school to understand issues relevant to society. Our conclusion corroborate the view that STS teaching contributes to the development of students' SL.